Implementation of a test to analyze PPO activity (PPO activity controls the darkening of flours and wheat products) - CGIAR Research Program on Wheat (2018)
Breeding lines analyzed already for PPO activity and data available for CIMMYT breeders and partners to start making selection for this trait.